MAPPING SPATIAL AND TEMPORAL CHANGES OF GLOBAL CORPORATE RESEARCH AND DEVELOPMENT ACTIVITIES BY CONDUCTING A BIBLIOMETRIC ANALYSIS - Csomós, György (Quaestiones Geographicae, 2017)
Corporate research and development (R&D) activities have long been highly concentrated in a handful of world cities. This is due to the fact that these cities (e.g., Tokyo, New York, London, and Paris) are home to the largest and most powerful transnational corporations and are globally important sites for innovative start-up firms that operate in the fastest growing industries. However, in tandem with the rapid technological changes of our age, corporate R&D activities have shifted towards newly emerging and now globally significant R&D centres, like San Jose, San Francisco, and Boston in the United States, and Beijing, Seoul, and Shenzhen in East Asia. In this paper, I will conduct a bibliometric analysis to define which cities are centres of corporate R&D activities, how different industries influence their performance, and what spatial tendencies characterise the period from 1980 to 2014. The bibliometric analysis is based upon an assumption that implies there is a close connection between the number of scientific articles published by a given firm and the volume of its R&D activity. Results show that firms headquartered in Tokyo, New York, London, and Paris published the largest combined number of scientific articles in the period from 1980 to 2014, but that the growth rate of the annual output of scientific articles was much greater in Boston, San Jose, Beijing, and Seoul, as well as some Taiwanese cities. Furthermore, it can also be seen that those cities that have the largest number of articles; i.e., that can be considered as the most significant sites of corporate R&D in which firms operate in fast-growing industries, are primarily in the pharmaceutical and information technology industries. For these reasons, some mid-sized cities that are home to globally significant pharmaceutical or information technology firms are also top corporate R&D hubs.